Analisis Perencanaan Pajak PPh 21 pada UMKM dalam Upaya Optimalisasi Pengelolaan Pajak Karyawan - Sri Rahayu; Dewi Ratna Sari; Mutia Dika Magdalena; Abdillah; Ibnu Hidayatullah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, including their contribution to government tax revenue. One of the tax obligations that must be fulfilled by MSMEs is Article 21 Income Tax (PPh 21) on employee income. This study aims to analyze Article 21 income tax planning in MSMEs as an effort to optimize employee tax management. The research employs a qualitative approach using a literature review method by examining tax regulations and relevant previous studies. The results indicate that Article 21 tax planning is a legal and effective strategy to optimize tax burdens without violating applicable tax laws. There are three methods of calculating Article 21 income tax, namely the gross, net, and gross-up methods. Based on the literature analysis, the gross-up method is considered the most optimal for MSMEs because the tax borne by the company can be recognized as a deductible expense, while employees continue to receive optimal take-home pay. However, the implementation of tax planning still faces several challenges, including limited tax knowledge, difficulties in selecting appropriate calculation methods, and obstacles in using digital tax systems. Therefore, improving tax literacy and strengthening administrative management are essential to support effective employee tax management in MSMEs